Strategi pengaplikasian gerakan teknik dasar roll depan dan roll belakang pada senam lantai yang benar kepada atlet pemula - Fikki Arifani Saputra; Nurul Aqil Nahari Fasy; Rohma Howo Nur Buwono; Tegar Pratama Dewa Putra; Naufal Pramuditya Ardhana; Idah Tresnowati (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
An article on dedication to floor gymnastics athletes through the iThe strategy for applying the basic forward roll and back roll techniques in floor gymnastics is correct for beginner’s in partnership with athletes located at the Persani Secretariat, district. Pemalang Jalan Acacia No. 18 villages in Pamutih sub-district, Ulujami Pemalang, there are 9 athletes who will take part in this service. The program that will be carried out together with partners is the iThe strategy for applying the basic forward roll and back roll techniques in floor gymnastics is correct for beginner’s. Friday 14 July 2023 from 16:00 WIB to 18:00 WIB on the grounds of the Persani Secretariat, Pemalang Regency. The results achieved from this activity are that floor gymnastics athletes have better